Biocompatibility of a restorative resin-modified glass ionomer cement applied in very deep cavities prepared in human teeth - Soares, Diana Gabriela [UNESP]; Basso, Fernanda Gonçalves; Scheffel, Débora Lopes Sales; Giro, Elisa Maria Aparecida; De Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri (My University, 2016)
This study evaluated whether a restorative resinmodified glass ionomer cement, Vitremer (VM), would be biocompatible with pulp tissue when used as a liner in very deep cavities prepared in young human permanent teeth. Two dental cements in current use as liner materials, Vitrebond (VB) and Dycal (DY), were compared to VM. Class V cavities were prepared in 36 sound premolars that were scheduled for extraction, and the cavity floor was lined with the restorative cement (VM) or a liner/base control cement (VB or DY). For VM specimens, the cavity floor was pretreated with a primer (polyacrylic acid plus 2-hydroxyethyl methacrylate). Teeth were extracted after 7 or 30 days and processed for microscopic evaluation. In the VM group, inward diffusion of dental material components through dentinal tubules, associated with disruption of the odontoblastic layer, moderate to intense inflammatory response, and resorption of inner dentin, was observed in 2 teeth at 7 days. These histologic features were observed in 1 tooth at 30 days. In the VB group, mild inflammatory reactions and tissue disorganization observed at 7 days were resolved at 30 days. No pulpal damage occurred in the DY specimens. Of the materials tested, only Vitremer was not considered biocompatible, because it caused persistent pulpal damage when applied in very deep cavities (remaining dentin thickness less than 0.3 mm).
Keywords: Biocompatibility; Dental materials; Glass ionomer cements; Pulp tissue